Genetic association of leukocyte telomere length with Graves’ disease in Biobank Japan: A two-sample Mendelian randomization study - Ye, Meijie; Wang, Yu; Zhan, Yiqiang (Frontiers in Immunology, 2022)
Background Telomere length (TL) has been recognized to be fundamental to the risk of autoimmune disorders. However, the role of leukocyte TL in Graves’ disease has not yet been fully elucidated. In the study, we exploited the two-sample Mendelian randomization (MR) design to evaluate the causal effect of leukocyte TL on the risk of Graves’ disease. Methods Genome-wide association study (GWAS) data of leukocyte TL from the Singapore Chinese Health Study (SCHS) cohort and Graves’ disease from Biobank Japan (BBJ, 2176 cases and 210,277 controls) were analyzed. Nine single nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs) for TL. We used the inverse variance weighted (IVW) approach as the main estimator and MR-Egger regression, weighted median, simple mode, and weighed mode methods as complementary estimators. Horizontal pleiotropy was assessed using the intercept from MR-Egger. Results The analysis demonstrated that genetically predicted longer leukocyte TL was causally associated with a lower risk of Graves’ disease using the IVW method (odds ratio [OR]: 1.64, 95% confidence interval [CI]: 1.23-2.17, P=2.27e-04, and other complementary MR approaches achieved similar results. The intercept from the MR-Egger analysis provided no noticeable evidence of horizontal pleiotropy (β=0.02, P=0.641). MR-PRESSO method reported no outliers (P=0.266). Conclusions Our results provided evidence to support a genetic predisposition to shorter leukocyte TL with an increased risk of Graves’ disease. Further studies are warranted to explore the mechanism underlying the association.